Characterising aerosol transport into the Canadian high Arctic using aerosol mass spectrometry and Lagrangian modelling - Kuhn, Thomas; Damoah, R.; Bacak, A.; Sloan, J.J. (Atmospheric Chemistry and Physics, 2010)
We report the analysis of measurements made using an aerosol mass spectrometer (AMS; Aerodyne Research Inc.) that was installed in the Polar Environment Atmospheric Research Laboratory (PEARL) in summer 2006. PEARL is located in the Canadian high Arctic at 610 m above sea level on Ellesmere Island (80° N 86° W). PEARL is unique for its remote location in the Arctic and because most of the time it is situated within the free troposphere. It is, therefore, well suited as a receptor site to study the long-range tropospheric transport of pollutants into the Arctic. Some information about the successful year-round operation of an AMS at a high Arctic site such as PEARL will be reported here, together with design considerations for reliable sampling under harsh low-temperature conditions. Computational fluid dynamics calculations were made to ensure that sample integrity was maintained while sampling air at temperatures that average 40 °C in the winter and can be as low as 55 °C. Selected AMS measurements of aerosol mass concentration, size and chemical composition recorded during the months of August, September and October 2006 will be reported. The air temperature was raised to about 20 deg;C during sampling, but the short residence time in the inlet system (∼25 s) ensured that less than 10% of semivolatiles such as ammonium nitrate were lost. During this period, sulfate was, at most times, the predominant aerosol component with on average 0.115 μg-3 (detection limit 0.003mg-3). The second most abundant component was undifferentiated organic aerosol, with on average 0.11 Î1/4g mg3 (detection limit 0.04 I1/4g mg3). The nitrate component, which averaged 0.007 mg-3, was above its detection limit (0.002 Î1/4g mg3), whereas the ammonium ion had an apparent average concentration of 0.02 g mg-3, which was approximately equal to its detection limit. A few episodes, having increased mass concentrations and lasting from several hours to several days, are apparent in the data. These were investigated further using a ...